The Brazilian Data Protection Law for LGBTQIA+ People: Gender identity and sexual orientation as sensitive personal data / A Lei Geral de Proteção de Dados Brasileira para Pessoas LGBTQIA+: Identidade de gênero e orientação sexual como dados pessoais sensíveis - de Souza Dantas Fico, Bernardo; Meng Nóbrega, Henrique (Revista Direito e Práxis, 2022)
DOI: 10.1590/2179-8966/2022/66817 Abstract Data protection laws are an advancement in protecting individuals but are not without criticism. Although discrimination on the grounds of "sexual orientation" and "gender identity" systemically violate LGBTQIA+’s fundamental rights and freedoms, the Brazilian National Congress failed to explicitly list either personal information as sensitive in the Brazilian General Data Protection Law. Exploring the hermeneutical flexibility of this law, this article argues that both "sexual orientation" and "gender identity" are under the sensitive data list. The aliases used in this protection are "sex life" and "race." A human rights-based interpretation of the former leads to the conclusion that "sex life" encompasses "sexual orientation" and/or "gender identity" due to, inter alia, human dignity and non-discrimination imperatives. In turn, Brazil's Supreme Court decisions have considered discrimination over "sexual orientation" and/or "gender identity" to be a form of social racism. Thus, while not explicitly listed, both "sexual orientation" and "gender identity" compose the list of sensitive data under LGPD. Keywords: Sexual orientation; Gender identity; Sensitive data; Human rights; Supreme Federal Court. Resumo Leis de proteção de dados pessoais são um avanço na proteção de indivíduos, mas não estão isentas de críticas. Embora discriminações com base em "orientação sexual" e "identidade de gênero" sistematicamente violem os direitos e liberdades fundamentais de LGBTQIA+, o Congresso Nacional não listou expressamente esses dados pessoais como sensíveis na Lei Geral de Proteção de Dados. Explorando a flexibilidade hermenêutica desta lei, este artigo argumenta que tanto "orientação sexual" como "identidade de gênero" são dados sensíveis, seja em virtude do termo "vida sexual", seja em virtude do termo "raça". Uma interpretação de “vida sexual” baseada em direitos humanos requer a inclusão de "orientação sexual" e "identidade de gênero" nesse termo por força, inter alia, de imperativos de dignidade da pessoa humana e não-discriminação. Por sua vez, o Supremo Tribunal Federal consolidou o entendimento de que discriminação baseada em “orientação sexual” e/ou “identidade de gênero” são formas de racismo social. Portanto, embora não expressamente listados, tanto “orientação sexual” quanto “identidade de gênero” compõem a lista de dados sensíveis sob a LGPD. Palavras-chave: Orientação sexual; Identidade de gênero; Dados sensíveis; Direitos humanos; Supremo Tribunal Federal.